Optimizing the role of androgen deprivation therapy in advanced prostate cancer: Challenges beyond the guidelines. Issue 6 (4th March 2020) - Shore, Neal D.; Antonarakis, Emmanuel S.; Cookson, Michael S.; Crawford, E. David; Morgans, Alicia K.; Albala, David M.; Hafron, Jason; Harris, Richard G.; Saltzstein, Daniel; Brown, Gordon A.; Henderson, Jonathan; Lowentritt, Benjamin; et al.
Abstract: Background: For specific clinical indications, androgen deprivation therapy (ADT) will induce disease prostate cancer (PC) regression, relieve symptoms and prolong survival; however, ADT has a well‐described range of side effects, which may have a detrimental effect on the patient's quality of life, necessitating additional interventions or changes in PC treatment. The risk‐benefit analysis for initiating ADT in PC patients throughout the PC disease continuum warrants review. Methods: A 14‐member panel comprised of urologic and medical oncologists were chosen for an expert review panel, to provide guidance on a more judicious use of ADT in advanced PC patients. Panel members were chosen based upon their academic and community experience and expertise in the management of PC patients. Four academic members of the panel served as group leaders; the remaining eight panel members were from Large Urology Group Practice Association practices with proven experience in leading their advanced PC clinics. The panel members were assigned to four separate working groups, and were tasked with addressing the role of ADT in specific PC settings. Results: This article describes the practical recommendations of an expert panel for the use of ADT throughout the PC disease continuum, as well as an algorithm summarizing the key recommendations. The target for this publication is all providers (urologists, medical oncologists, radiation oncologists, or advanced practice providers) who evaluate and manage advanced PC patients, regardless of their practice setting. Conclusion: The panel has provided recommendations for monitoring PC patients while on ADT, recognizing that PC patients will progress despite testosterone suppression and, therefore, early identification of conversion from castrate‐sensitive to castration resistance is critical. Also, the requirement to both identify and mitigate side effects of ADT as well as the importance of quality of life maintenance are essential to the optimization of patient care, especially as more combinatorial therapeutic strategies with ADT continue to emerge.